The Impact of Ambon Banana (Musa Accuminata Colla) Puree Addition to Banana Bread Making on Physical Quality and Consumer Acceptance - Roziyah, Pipit; Artanti, Guspri Devi; Cahyana, Cucu (Sahabat Publikasi, 2024)
The objective of this study was to analyze the impact of the addition of ambon banana puree in banana bread on physical quality and consumer acceptance. The method used was an experimental method with three types of treatments, namely banana bread adding 25%, 50%, and 75% ambon banana puree, conducted at the Pastry & Bakery Laboratory of Culinary Art Education, State University of Jakarta. The validity test was conducted using the organoleptic test to five lecturers of Culinary Art Education, State University of Jakarta, consisting of four external aspects and eight internal aspects, showing that banana bread adding 25% and 50% ambon banana puree excelled in various aspects. The physical quality test was conducted by measuring the volume of each product for three repetitions. The test results using the ANOVA test showed that there was no impact of the addition of banana puree on the quality of bread volume. The consumer acceptance test was conducted using the Friedman test, and data collection was done using the hedonic test for 30 panelists. The Friedman test results showed that there was an impact of the addition of ambon banana puree in banana bread on consumer acceptance in the aspects of volume, skin color, bread crust, skin characteristics, crumb color, crumb pores, crumb texture, and chewing quality. Furthermore, the results of Tuckey's test showed that banana bread adding 25% ambon banana puree was most preferred in terms of volume and chewing quality, banana bread adding 25% and 50% ambon banana puree was most preferred in terms of bread crust color, bread crust thickness, bread crust characteristics, crumb color, crumb pores, and crumb texture. Based on the results of this study, it is recommended that banana bread add 50% of banana puree products for further utilization of banana ambon.